Approaches to Defining Healthy Diets: A Background Paper for the International Expert Consultation on Sustainable Healthy Diets. Issue 2 (December 2020) - Kumanyika, Shiriki; Afshin, Ashkan; Arimond, Mary; Lawrence, Mark; McNaughton, Sarah A.; Nishida, Chizuru
Background: Healthy diets promote optimal growth and development and prevent malnutrition in all its forms, including undernutrition, obesity, and diet-related noncommunicable diseases (NCDs). Objective: This background paper for the International Expert Consultation on Sustainable Healthy Diets characterizes healthy diets and their implications for food system sustainability. Methods: Three complementary approaches to defining healthy diets are compared: World Health Organization (WHO) guidelines or recommendations developed between 1996 and 2019; 2017 Global Burden of Disease (GBD) risk factor study estimates of diet-related risk–outcome associations; and analyses associating indices of whole dietary patterns with health outcomes in population studies and clinical trials. Results: World Health Organization dietary recommendations are global reference points for preventing undernutrition and reducing NCD risks; they emphasize increasing intakes of fruits, vegetables (excepting starchy root vegetables), legumes, nuts, and whole grains; limiting energy intake from free sugars and total fats; consuming unsaturated rather than saturated or trans fats; and limiting salt intake. Global Burden of Disease findings align well with WHO recommendations but include some additional risk factors such as high consumption of processed meat; this approach quantifies contributions of diet-related risks to the NCD burden. Evidence on whole dietary patterns supports WHO and GBD findings and raises concerns about potential adverse health effects of foods with high levels of industrial processing. Conclusions: Implied shifts toward plant foods and away from animal foods (excepting fish and seafood), and for changes in food production systems have direct relevance to the sustainability agenda.